Implikasi Pembentukan Daerah Persiapan Otonom Baru Berdasarkan Undang-Undang Nomor 23 Tahun 2014 - Bagio Kadaryanto (Al-Risalah, 2017)
Consequences of the implementation of the Act Number 23 of 2014 on Regional Government spawned extraordinary complexity of the problems in some areas. One of the problems that arise is a rampant discourse of regional expansion that occurs both at the provincial and district/city. In essence, the establishment, merger, and abolition of the area aim to improve public services to be more optimal, shorten the span of control, and accelerate the welfare of society in strengthening the integrity of the Unitary Republic of Indonesia. The purpose of this study was to determine the implications of the establishment of new autonomous regions in the frame of the Republic of Indonesia based on Act Number 23 of 2014 on Regional Government; and to understand the implications of the establishment of new autonomous regions preparation for improving people's welfare by Act Number 23 of 2014 on Regional Government. This type of research is a normative legal research. Methods and techniques of data collection through library studies or studies document. Mechanicalanalysis of legal material is a descriptive qualitative. Conclusions from this research are that the implications of the establishment of regional preparation of new autonomous within the framework of the Unitary Republic of Indonesia before Act Number 23 of 2014 on Regional Government due to the local communities feel there is an imbalance of equity and fairness between regions with each other in the local government areas. Implications of the establishment of new autonomous regions preparation for improving people's welfare by Act Number 23 of 2014 on Regional Government that in order to establish an area or region of the expansion needed a measure as the basis for the determination. Establishment and expansion of new areas should be based on the divisions that are objective with those aspects of the financing of Human Resources and other support facilities.